Analysis of Needs for the Development of Integrated Interactive Learning Media Soft Skills Ready for Work Based in Vocational High Schools - Anggi Alfioni; Mukhlisin, Mukhlisin; Nur, Hasanah; Sukma, Indra (Cita konsultindo, 2025)
Vocational education through Vocational High Schools (SMK) in Indonesia plays a strategic role in preparing a skilled workforce that is ready to compete in the industrial world. This research aims to analyze the need for the development of Interactive Learning Media (MPI) that is integrated with web-based job-ready soft skills for vocational school students. This type of research is a Mixed Methods research that aims to produce descriptive data that combines qualitative and quantitative. This research was carried out at SMKN 4 Buru, SMKN 7 Buru, SMK Nasional Makassar and SMK Telkom Makassar. The research sample consisted of 90 students who were selected in total sampling from 2nd grade students of SMKN 4 Buru, SMKN 7 Buru, Makassar National Vocational School and Telkom Makassar Vocational School. This study analyzes the need for soft skill development in vocational school students to face the world of work. The observation results showed that most students (93.5%) considered soft skills very important, especially Work Ethics (97%), Teamwork (93%), and Communication Skills (92%). Soft skill learning in vocational schools is still limited to theory and does not involve field practice and adequate evaluation. Learning technology is recognized to improve soft skills (89.2%), although a small percentage of students feel less effective (10.8%). Students prefer interactive and experiential learning (77%), but face barriers to accessing technology (26.4%). A web-based interactive learning model that integrates job-ready soft skills can address this gap by increasing student engagement, providing flexibility, and supporting collaboration with the industry.